Pulverized Water Hyacinth as an Admixture for Concrete - Abana, Ertie; Vega, William; Gacias, Jaezel; John RaÃ±on, Patrick; Talattad, John Denver; Orata, Herbert; Perez, Jerone (International Journal of Integrated Engineering, 2021)
This study sought to evaluate the setting time and strength property of concrete when pulverized water hyacinth serves as an admixture by weight. The materials used in this study included water hyacinth plants, cement, coarse and fine aggregates. Dried water hyacinth was pulverized and added to the concrete with two different percentages in each mixture. A standard mixture without water hyacinth was also created for comparison with the concrete cylinders with mixture that has pulverized water hyacinth. The first concrete cylinder contains 0.5% of pulverized water hyacinth by weight and the second concrete cylinder contains 1% of pulverized water hyacinth by weight. The curing was done for 28 days, and the properties of the concrete cylinders, namely setting time and strength, were recorded.  It was revealed in the setting time test that the concrete with 0.5% pulverized water hyacinth may serve as accelerator for concrete while the concrete cylinder with 1% pulverized water hyacinth by weight can be a retarder. Moreover, the concrete cylinders with water hyacinth have better compressive strength than that of the concrete cylinder without pulverized water hyacinth.